Examining Pace of Economic Growth in India under Globalized Trade Regime and International Economic Integration (International Journal of Food and Nutritional Sciences, 2021)
The present research paper examines unique pace of economic growth under globalized trade regime and international economic integration, taking India as the case studied. In its first component, it discusses the literature in theoretical-cum-historical aspects of globalization and the structure of Indian Economy. In the section that follows, it takes up the statistical aspects related to the growth performance of the Indian Economy. It uses the annual time series data to explore the effect of globalization and pandemic on the Indian economy. The results show that there is a symbolic melioration in India’s socio-economic development. India has done well in GDP growth, shown resilience to external shocks of COVID-19 virus and accomplished significant accumulation of foreign exchange reserves. Following the unique path of economic refinements, India commenced to turn up as a competitor of some importance across the Globe. It had grown as one of the fastest emerging economies across the world economy and a most preferred terminal of global foreign direct investment.